PERTUMBUHAN KEDELAI (Glycinemax (L.) Merril) VARIETAS ANJASMORO DENGAN PEMBERIAN PUPUK ORGANIK CAIR BONGGOL PISANG KEPOK (Musa acuminata L.) - Siti Hodijah; Mukarlina Mukarlina; Elvi Rusmiyanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The increase in consumption needs for soybeans makes the production level must be optimal. The quality production of soybean plants requires nutrients to increase growth. The need for soybeans in West Kalimantan is increasing yearly, but its growth on peat soils is still not optimal. This study aims to determine the effect of liquid organic fertilizer (POC) from the banana hump on soybean plants' growth and the concentration that produces the best growth. This research method used a completely randomized design (CRD) with six treatments and four replications, so there were 24 treatments. The concentrations used in this study were 0 ml/L, 40 ml/L, 80 ml/L, 120 ml/L, 160 ml/L and 200 ml/L. The data was analyzed using one-way ANOVA with Duncan's further test. Parameters significantly different in this study were plant height, number of leaves, number of branches, shoot weight, and dry weight. The concentration that produced the best growth was 160 ml/L.